Hemodynamic Response and Patient Comfort in Conscious Intubation with Recurrent Laryngeal Nerve Block - Rapa, Fransiscus Braveno; Adinda Putra Pradhana (HM Publisher, 2023)
Introduction: Anesthetic management of conscious intubation in difficult airway cases can be done with topical anesthetics, airway nerve blocks, or a combination of both. Inadequate quality of anesthesia can cause hemodynamic turmoil, pain, gag reflex, and patient discomfort. This study presents a case report on the use of recurrent laryngeal nerve blocks in patients who were consciously intubated. Case presentation: This man was premedicated in the reception room using 10 mg IV dexamethasone, 10 mg IV diphenhydramine, 2 drops of 0.05% oxymetazoline right nose, 4 ml of 4% lidocaine nebulization, 10% lidocaine spray on the uvula and 2 puffs of pharyngopalatine fauces. Once in the operating room, this man was given midazolam 1.5 mg IV, fentanyl 25 mcg IV, followed by ultrasound-guided recurrent laryngeal nerve block. The local anesthetic used was 2 ml of 2% lidocaine. After that, right intranasal conscious intubation was performed. During intubation, this man began to show discomfort in the form of frowning when the flexible scope (FIS) was in the larynx and briefly passed the vocal cords. In addition, a gag reflex and cough are seen when the FIS and airways pass over the larynx and vocal cords. Intubation is done in about 4 minutes with 1 attempt. Conclusion: Awake intubation can be performed with topical anesthesia, airway block, or a combination of the two. Awake intubation with a combination of laryngeal recurrent nerve blocks and topical anesthesia, in this case, was inadequate because there was coughing, gag reflex, and increased heart rate during intubation.